Enhancing photocatalytic activity for visible-light-driven H2 generation with the surface reconstructed LaTiO2N nanostructures. (March 2015) - Li, Yaguang; Cheng, Xuanbing; Ruan, Xueyuan; Song, Hui; Lou, Zirui; Ye, Zhizhen; Zhu, Liping
Abstract: LaTiO2 N is known as a 600 nm-light-sensitive photocatalyst for water oxidation rather than H2 generation. Although great efforts have been made, the H2 evolution quantum yield is still limited. Herein, the hollow sphere LaTiO2 N nanostructures are synthesized, and the H introduced lattice disorder is formed on the surface of the H2 treated LaTiO2 N nanostructures. Owing to the ultrathin thickness of shell and surface reconstruction, the H2 treated LaTiO2 N nanostructures could passivate the recombination of photo-generated carriers and the quantum efficiency for H2 generation can be as high as 3.4% under visible light irradiation. Graphical abstract: Highlights: The LaTiO2 N nanostructures in hollow sphere morphology are synthesized successfully. The H2 treated LaTiO2 N nanostructures have a disordered surface layer. The H introduced surface has the passivation effect on the surface recombination of photo-generated carriers. The H2 treated Pt/LaTiO2 N nanostructures have 3.4% quantum efficiency for H2 generation under visible light irradiation.